2006
DOI: 10.1542/peds.2006-2588
|View full text |Cite
|
Sign up to set email alerts
|

Patient- and Family-Centered Care and the Role of the Emergency Physician Providing Care to a Child in the Emergency Department

Abstract: Patient-and family-centered care is an approach to health care that recognizes the role of the family in providing medical care; encourages collaboration between the patient, family, and health care professionals; and honors individual and family strengths, cultures, traditions, and expertise. Although there are many opportunities for providing patient-and family-centered care in the emergency department, there are also challenges to doing so. The American Academy of Pediatrics and the American College of Emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Social, cultural, economic, psychological, and educational parameters are essential for mutual interactions within a family. [ 12 ] Parrish et al stated in their studies that the parent is the most critical link between the patient and practitioner for a successful outcome in treating pediatric patients. In line with these scientific anecdotes, previous publications have reported that although malignant breast disease in children is sporadic, the idea that their children may have permanent breast damage or suspicion of malignancy may cause psychological trauma and anxiety in parents who apply to relevant centers due to breast problems in their children.…”
Section: Discussionmentioning
confidence: 99%
“…Social, cultural, economic, psychological, and educational parameters are essential for mutual interactions within a family. [ 12 ] Parrish et al stated in their studies that the parent is the most critical link between the patient and practitioner for a successful outcome in treating pediatric patients. In line with these scientific anecdotes, previous publications have reported that although malignant breast disease in children is sporadic, the idea that their children may have permanent breast damage or suspicion of malignancy may cause psychological trauma and anxiety in parents who apply to relevant centers due to breast problems in their children.…”
Section: Discussionmentioning
confidence: 99%
“…Family-centred care is the collaboration of healthcare providers, patients, and families to optimize the quality of care [ 5 ]. It is well established in critical care [ 9 ] and paediatric emergency [ 10 ]. Family-centred care strategies in cardiac arrest care are believed by some to be a strategy to improve outcomes for patients and families [ 11 , 12 ] yet barriers to their adoption in the prehospital setting have been identified [ 13 ].…”
Section: Clinician’s Capsulementioning
confidence: 99%
“…HBCR program is the standard of practice that results in high-quality services. HBCR program embraces the concepts that, (a) we are providing care for a person, not a condition, (b) the patient is best understood in the context of his or her family, culture, values, and goals, and (c) honoring that context will result in optimal health care, safety, and patient satisfaction ( American Academy of Pediatrics, 2006 ; Dunn et al, 2006 ). In the UK, HBCR with a self-help manual—the heart manual—supported by a nurse facilitator is a program of CR that has been available for years.…”
Section: Introductionmentioning
confidence: 99%